Sex-Specific Equations to Estimate Maximum Oxygen Uptake in Cycle Ergometry - Silva, Christina G. de Souza e (Arq Bras Cardiol, 2015)
BACKGROUND: Aerobic fitness, assessed by measuring VO(2)max in maximum cardiopulmonary exercise testing (CPX) or by estimating VO(2)max through the use of equations in exercise testing, is a predictor of mortality. However, the error resulting from this estimate in a given individual can be high, affecting clinical decisions. OBJECTIVE: To determine the error of estimate of VO(2)max in cycle ergometry in a population attending clinical exercise testing laboratories, and to propose sex-specific equations to minimize that error. METHODS: This study assessed 1715 adults (18 to 91 years, 68% men) undertaking maximum CPX in a lower limbs cycle ergometer (LLCE) with ramp protocol. The percentage error (E%) between measured VO(2)max and that estimated from the modified ACSM equation (Lang et al. MSSE, 1992) was calculated. Then, estimation equations were developed: 1) for all the population tested (C-GENERAL); and 2) separately by sex (C-MEN and C-WOMEN). RESULTS: Measured VO(2)max was higher in men than in WOMEN: -29.4 ± 10.5 and 24.2 ± 9.2 mL.(kg.min)(-1) (p < 0.01). The equations for estimating VO(2)max [in mL.(kg.min)(-1)] were: C-GENERAL = [final workload (W)/body weight (kg)] x 10.483 + 7; C-MEN = [final workload (W)/body weight (kg)] x 10.791 + 7; and C-WOMEN = [final workload (W)/body weight (kg)] x 9.820 + 7. The E% for MEN was: -3.4 ± 13.4% (modified ACSM); 1.2 ± 13.2% (C-GENERAL); and -0.9 ± 13.4% (C-MEN) (p < 0.01). For WOMEN: -14.7 ± 17.4% (modified ACSM); -6.3 ± 16.5% (C-GENERAL); and -1.7 ± 16.2% (C-WOMEN) (p < 0.01). CONCLUSION: The error of estimate of VO(2)max by use of sex-specific equations was reduced, but not eliminated, in exercise tests on LLCE.